Tumor-derived CCL20 affects B16 melanoma growth in mice. Issue 1 (January 2020) - Martin-Garcia, Diego; Silva-Vilches, Cinthia; Will, Rainer; Enk, Alexander H.; Lonsdorf, Anke S.
Highlights: Pro-inflammatory cytokines may upregulate CCL20 expression of melanoma cells. CCL20 expression by B16 melanoma results in reduced local tumor growth. CCR6 expression by melanoma cells and host may affect local tumor growth in mice. Abstract: Background: Chemokine ligand-20 (CCL20) expressed in the epidermis is a potent impetus for the recruitment of CC-chemokine receptor 6 (CCR6)-expressing subsets of DCs, B-cells and memory T-cells into the skin. CCL20 and CCR6+ immune cells have been detected in chronic inflammatory skin diseases and several malignancies, including melanoma. Yet, the functional contribution of the CCR6/CCL20 axis for melanoma progression remains controversial. Objective: The functional contribution of CCR6-expressing immune cell subsets and local CCL20 in the tumor microenvironment for the immune control of melanoma was studied. Methods: Homeostatic and inducible CCL20 secretion of murine (B16, Ret) and human (A375, C32) melanoma cells was analyzed by ELISA. To assess the functional relevance of CCR6/CCL20 interactions on local tumor progression, prestimulated or retrovirally transduced B16/F1 melanoma cells overexpressing CCL20 (B16-CCL20) were injected subcutaneously into C57BL/6 Wt mice and congenic CCR6-deficient (CCR6 −/− ) mice. Infiltrating leucocytes were examined by flow cytometry in tumors and draining lymph nodes (DLNs). Results: Melanoma cell lines up-regulate CCL20 secretion upon stimulation with pro-inflammatory cytokines in vitro. While only moderate changes in phenotype and composition of leucocytes were detected in advanced tumors and DLNs, mice injected with CCR6+ B16-CCL20 cells developed smaller tumors compared to B16-Control injected littermates, with CCR6-/- mice displaying the most pronounced reduction in tumor growth and incidence. Conclusion: Our results suggest that CCR6/CCL20 interactions and individual independent effects of CCL20 and CCR6 in the microenvironment may be essential for melanoma progression and suggest a decisive role of this chemokine axis for melanoma pathogenesis beyond chemoattraction.